2007
DOI: 10.1002/jbm.a.31477
|View full text |Cite
|
Sign up to set email alerts
|

A novel, tissue occlusive poly(ethylene glycol) hydrogel material

Abstract: The use of guided bone regeneration (GBR) techniques requires new materials meeting the needs of clinical application. Design criteria for GBR devices are biocompatibility, tissue occlusion, space provision, and clinical manageability. This study evaluates a novel biodegradable poly (ethylene glycol) (PEG) based material as tissue occlusive membrane. A subcutaneous implant model in rats was developed to test the barrier function of the PEG hydrogels over time. Fourteen rats received three membrane implants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 18 publications
4
68
2
Order By: Relevance
“…The PEG material can be designed cell‐occlusive and as matrix formulation (Wechsler et al. ; Hou et al. ).…”
mentioning
confidence: 99%
“…The PEG material can be designed cell‐occlusive and as matrix formulation (Wechsler et al. ; Hou et al. ).…”
mentioning
confidence: 99%
“…In particular, hydrogel formation is based on a cross‐linking reaction of two PEG compounds and proceeds fast and selectively at physiological temperature and pH (Elbert et al 2001). Experimental data provide clear evidence that PEG hydrogels are highly biocompatible, cell‐occlusive and biodegradable (Jung et al 2006, Wechsler et al 2008, Herten et al 2009, Thoma et al 2009). Moreover, animal and clinical studies have indicated that a PEG hydrogel membrane may be as effective as a native collagen membrane to predictably support bone regeneration in dehiscence‐type defects in conventional SLA titanium implants (Jung et al 2009a, b).…”
mentioning
confidence: 99%
“…[ 39 ] As many vaccines are administered in alum-adsorbed form, the depot-based strategy described here will likely be generally applicable to other vaccines or even to other classes of pharmaceuticals like growth factors or antibodies that can easily be incorporated into biohybrid hydrogels. [ 40 , 41 ] Based on this fl exibility in the cargo pharmaceutical combined with the potential of using different scFvs as described above, the present study likely represents a generic blueprint for the design of remotecontrolled hydrogel drug depots for the patient compliant delivery of the ever growing number of biopharmaceuticals.…”
Section: Discussionmentioning
confidence: 99%